1997
DOI: 10.1128/aac.41.5.1099
|View full text |Cite
|
Sign up to set email alerts
|

Unique intracellular activation of the potent anti-human immunodeficiency virus agent 1592U89

Abstract: The anabolism of 1592U89, (-)-(1S,4R)-4-[2-amino-6-(cyclopropylamino)-9H-purin-9-yl]-2-cyclo pentene-1-methanol, a selective inhibitor of human immunodeficiency virus (HIV), was characterized in human T-lymphoblastoid CD4+ CEM cells. 1592U89 was ultimately anabolized to the triphosphate (TP) of the guanine analog (-)-carbovir (CBV), a potent inhibitor of HIV reverse transcriptase. However, less than 2% of intracellular 1592U89 was converted to CBV, an amount insufficient to account for the CBV-TP levels observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
108
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(111 citation statements)
references
References 37 publications
3
108
0
Order By: Relevance
“…IEC using high-salt concentrations was first described in the 1950s [12]. Long run times [11,13] and incompatibility with mass spectrometry, however, have limited its application for nucleotide quantification mostly to in vitro studies [14].…”
Section: Introductionmentioning
confidence: 99%
“…IEC using high-salt concentrations was first described in the 1950s [12]. Long run times [11,13] and incompatibility with mass spectrometry, however, have limited its application for nucleotide quantification mostly to in vitro studies [14].…”
Section: Introductionmentioning
confidence: 99%
“…The generated nucleosides were analyzed by using LC/UV, radioimmunoassay, and LC-MS/MS [3][4][5][6]. Strong anion-exchange HPLC has also been used to isolate and directly analyze nucleotides [7,8]. However, because of its long run time and requirement for radiometric detection, the application of the anion-exchange chromatographic method has been limited mainly to in vitro…”
mentioning
confidence: 99%
“…Another challenge for rapid detection of the adenosine nucleotides is that low detection limits are often needed because the compounds are generally present at submicromolar levels in cells [13][14][15][16]. Mass spectrometry coupled with HPLC has become widely used for high-throughput analysis in pharmaceutical industry due to its high specificity and sensitivity [7,8,17,18]. The high selectivity of MS and MS/MS techniques provides great separation and detection power, making them attractive alternatives for the trace analysis of nucleotides.…”
mentioning
confidence: 99%
“…ABC is first phosphorylated by adenosine phosphotransferase (AdoPT) into the cell to ABC monophosphate (Scheme 6), which is then converted to Carbovir monophosphate (CBV-MP), by the enzyme adenosine deaminase-like protein isoform 1 (ADAL1), recently identified to play a physiological role in the salvage routes of 6-substituted purine-or 2-aminopurine nucleoside monophosphate (Murakami et al, 2011). Finally, CBV-MP is anabolised to CBV-TP, a potent inhibitor of HIV-RT that acts both as a competitive inhibitor of dGTP for DNA incorporation and as a DNA chain terminator (Faletto et al, 1997;Stankova et al, 2012). Boyle et al (2012) reported the synthesis of ABC from the β-lactame (2) obtained by [2 + 2] cycloaddition of chlorosulphonyl isocyanate with cyclopentadiene (Scheme 5b) and subsequent Lipolase (a soluble preparation of Thermonyces lanuginosus lipase, produced by submerged fermentation of a genetically modified Aspergillus oryzae microorganism) catalysed kinetic resolution.…”
Section: As Nucleoside Prodrugsmentioning
confidence: 99%